Animal Models, Learning Lessons to Prevent and Treat Neonatal Chronic Lung Disease - Jobe, Alan H. (Frontiers in Medicine, 2015)
Bronchopulmonary dysplasia (BPD) is a unique injury syndrome caused by prolonged injury and repair imposed on an immature and developing lung. The decreased septation and decreased microvascular development phenotype of BPD can be reproduced in newborn rodents with increased chronic oxygen exposure and in premature primates and sheep with oxygen and/or mechanical ventilation. The inflammation caused by oxidants, inflammatory agonists, and/or stretch injury from mechanical ventilation seems to promote the anatomic abnormalities. Multiple interventions targeted to specific inflammatory cells or pathways or targeted to decreasing ventilation-mediated injury can substantially prevent the anatomic changes associated with BPD in term rodents and in preterm sheep or primate models. Most of the anti-inflammatory therapies with benefit in animal models have not been tested clinically. None of the interventions that have been tested clinically are as effective as anticipated from the animal models. These inconsistencies in responses likely are explained by the antenatal differences in lung exposures of the developing animals relative to very preterm humans. The animals generally have normal lungs while the lungs of preterm infants are exposed variably to intrauterine inflammation, growth abnormalities, antenatal corticosteroids, and poorly understood effects from the causes of preterm delivery. The animal models have been essential for the definition of the mediators that can cause a BPD phenotype. These models will be necessary to develop and test future-targeted interventions to prevent and treat BPD.